2012
DOI: 10.1186/1472-6823-12-21
|View full text |Cite
|
Sign up to set email alerts
|

Insulin analogues dosing and costs - comparing real-life daily doses of insulin detemir and insulin glargine in type 2 diabetes patients

Abstract: BackgroundThe uncertainties regarding dose similarities between basal long-acting insulin analogues remain. Recent real-world studies indicate dose similarities between insulin detemir and insulin glargine, but further studies are still warranted.The aim of this study was to compare real-life daily doses of insulin detemir and insulin glargine in type 2 diabetes patients when administered once daily.MethodsWe analysed 536 patient cases from general practice (63%) and endocrinological outpatient clinics (37%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…However, a comparison of once-daily dosing of both basal insulins in type 2 diabetes suggested that a higher dose requirement for insulin detemir was required versus insulin glargine 13 . While yet other studies have demonstrated that dosing for insulin detemir and insulin glargine is similar once settings and dosing frequency are taken into account [14][15][16] , our observations are nevertheless consistent with the notions of both twice-daily administration increasing the basal insulin dose requirement, and of insulin detemir having a lower unit potency.…”
Section: Discussionsupporting
confidence: 90%
“…However, a comparison of once-daily dosing of both basal insulins in type 2 diabetes suggested that a higher dose requirement for insulin detemir was required versus insulin glargine 13 . While yet other studies have demonstrated that dosing for insulin detemir and insulin glargine is similar once settings and dosing frequency are taken into account [14][15][16] , our observations are nevertheless consistent with the notions of both twice-daily administration increasing the basal insulin dose requirement, and of insulin detemir having a lower unit potency.…”
Section: Discussionsupporting
confidence: 90%
“…Other observational studies have used "real-life" comparisons in which data were obtained through provider questionnaires. [21][22][23] Often providers were not selected at random and may have possessed bias toward either basal insulin. 21 With respect to dosing equivalency, results of these studies should be interpreted with caution given the subjective nature of data collection and relatively uncontrolled environment of these studies.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Basal insulin formulations have been continuously improved over the years and have become widely used as they have many pharmacodynamic and pharmacokinetic advantages over neutral protamine Hagedorn (NPH) insulin including a longer duration of action, reduced variable absorption profiles and a reduced marked peak effect [ 3 ]. Insulin detemir and insulin glargine are widely used as add-on therapies for patients not responding to oral anti-diabetic drug (OAD) regimens, but there are few studies directly comparing the two insulin analogues in routine care [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%